Is Inherited Thrombphilia in Pregnancy a Risk Factor for Familial Stroke? - Seyed Shamseddin Hejazi; Azimi, Cyrus; Sabokbar, Tayebeh; Shakoori, Abbas (International Journal of Medical Research, 2013)
Context: Inherited thrombophilia is an abnormality of blood coagulation that increases the risk of thromboembolic disease. During pregnancy, the thrombogenic potential of this inherited disorder is enhanced because of the hypercoagulable state produced by normal pregnancy-associated changes in several coagulation factors. Aims: The purpose of this research was to find the association of polymorphisms and mutations of coagulation factors. Settings and Design: This Study is the first comprehensive study of thrombophilia genes in the Iranian population. Methods and Material: This current research was performed in a group of 70 women referred to the Department of Medical Genetics. due to reproductive failures with history of thrombosis in pregnancy, First degree families have a history of heart attacks and strokes. The clinical data on family history of diabetes, high cholesterol, high blood pressure, a history of recurrent pregnancy loss has been observed. Results: The most common mutation was PAI-1 with (62.9 %) heterozygote 4G/5G alleles and (14.3%) homozygote 4G/4G alleles. The second and third mutations were MTHFR-C677 T with (44.3%) heterozygote and (8.6%) homozygotes and MTHFR-1298 C with (41.4%) heterozygotes and (12.9%) homozygotes. Conclusions: These data indicate that polymorphic variation in the prevalence of thrombophilia in women with recurrent miscarriage with our population has had a lot of different European populations. Mutations in this gene in the percentage of individuals who have a family history of stroke or heart rate have been observed.